Bibliometric Analysis of Research on Women’s Labor Force Participation and Household Economics - Dupi, Muhamad; Baloch, Inayat Ullah (UI Scholars Hub, 2026)
Studies of women labor participation (WLFP) and household economics have grown in size in the last two decades and more research and policy focus are given to gender equality, labor markets and household welfare. Nevertheless, the available literature is still in pieces by region, theme, and institutional settings and a complete bibliometric review of this area of study is yet to be done. The objective of the proposed study is to trace the world-wide literature on the topic of women participation in the labor force and household economics through the analysis of the patterns of publications, networks of cooperations, and the development of the topic. The research design adopted in this study is bibliometric research design, which focuses on the analysis of 502 peer-reviewed journal articles, which have been indexed in the Scopus database and published in the English language between 2000 and 2025. The bibliographic data was processed and visualized using VOSviewer (version 1.6.20) and co-authorship analysis, bibliographic coupling, and keyword co-occurrence analysis were used to determine the influential countries, institutions, journals, and publications as well as strong research themes.The results show that the research output has been increasing steadily, and especially at the beginning of the COVID-19 period. Nevertheless, the high concentration of scholarly production and collaboration in Global North countries and the few and loosely-connected contributions of the Global South lead to a high level of control over the field. Thematic evolution demonstrates the progressive development of the general socio-demographic visions to more pragmatic ones, which are the household income, participation in the labor market, and the distribution of income.